University students' perceptions of interactive response system in an English language course: a case of Pear Deck - Kiki Juli Anggoro; Damar Isti Pratiwi (Association for Learning Technology, 2023)
Pear Deck is one interactive response system that has gained popularity in recent years. This study addressed the gap in the literature and considered students' experience of the platform in a Thai university context. This was a mixed-method study in which 320 students completed a survey including closed and open-ended components. Quantitative data measuring students' perceptions using Likert-scale surveys were collected, while qualitative data were used to get a deeper understanding of students' experience in learning using Pear Deck in the classroom. The data were analysed based on gender differences and students' proficiency levels. According to the findings of this study, students' perceptions were not significantly different based on gender. However, despite the finding that both basic and independent users had good attitudes towards the platforms, the latter group gave a substantially higher score. Furthermore, the study revealed that the students had a favourable impression of Pear Deck. They believed that the platform was engaging, easy to use, and had the potential to aid learning.